PENGEMBANGAN METODE ILMIAH DALAM PENAFSIRAN FILSAFAT ILMU - Indah Permata Sari; Azmi Fitrisi; Ofianto Ofianto (Ensiklopedia of Journal, 2023)
The development of the Scientific Method in the interpretation of the Philosophy of Science are 2 matters that have a strong attachment. Scientific provisions are very binding on the philosophy of science related to the scientific method itself. There are several dimensions or aspects so that science has objects in the scientific method, including 1) Ontology, 2) Axiology, and 3) Epistemology. Inductive mindset and deductive mindset are the ways of thinking used in the scientific method itself, including formulating problems, conducting library research, formulating hypotheses, testing hypotheses, gathering information, analyzing and interpreting information, finally drawing conclusions. There are several schools of thought and paradigms in the philosophical world related to research, including: positivism, post-positivism, constructivism and pragmatism. These views have an influence on research participants. Science has a significant role in the development of scientific methods by leading to qualitative, quantitative and combined research methods. This is evident from the implications and contributions in the development of scientific procedures, including: a, the philosophy of science provides guidelines for a person to distinguish between all matters that are scientific or not, so that solutions are found for these cases. b, purpose, the philosophy of science in the development of scientific procedures can provide a logical study of every science that is studied and can share a clear orientation and values for each scientific discipline. c, through the philosophy of science one finds guidance in a reflective manner and research and reasoning so that one can balance logic, experience, reason and religion in achieving a prosperous life. d, the philosophy of science shares the principles of scientific procedures, because the scientific method that is developed must be accountable logically and rationally, so that it can be used universally.Keywords: Development, scientific method, philosophy of science